2007
DOI: 10.1086/510745
|View full text |Cite
|
Sign up to set email alerts
|

Options for a Second-Line Antiretroviral Regimen for HIV Type 1-Infected Patients Whose Initial Regimen of a Fixed-Dose Combination of Stavudine, Lamivudine, and Nevirapine Fails

Abstract: After experiencing treatment failure with a fixed-dose combination of stavudine, lamivudine, and nevirapine, almost all patients have lamivudine and nonnucleoside reverse-transcriptase inhibitor resistance. The options for a second-line regimen are limited for one-half of these patients. In resource-limited settings where availability of antiretroviral agents is limited, strategies for prevention of HIV-1 resistance are crucial. Early detection of virological failure may provide more options and better treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
143
3
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(162 citation statements)
references
References 31 publications
14
143
3
2
Order By: Relevance
“…Our previous study has shown that Y181C and K103N are common drug-resistance mutations after failing the first-line ART in Thailand. 24 To minimize TDR in Thailand, strengthening of HIV care system, supporting patient's adherence to therapy, and prevention of HIV transmission in both HIV-infected and not infected individuals are crucial. Regular surveillance of TDR in Thailand will inform evidence-based decision making regarding NAP.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has shown that Y181C and K103N are common drug-resistance mutations after failing the first-line ART in Thailand. 24 To minimize TDR in Thailand, strengthening of HIV care system, supporting patient's adherence to therapy, and prevention of HIV transmission in both HIV-infected and not infected individuals are crucial. Regular surveillance of TDR in Thailand will inform evidence-based decision making regarding NAP.…”
Section: Discussionmentioning
confidence: 99%
“…The late switching may result in poor response to Tenofovir based regimen which is used for second line in India due to accumulating thymidine associated mutations-TAM's. Many studies from Africa and Thailand [6]- [8], only 8% to 40% of individuals who present with evidence of immunological failure had virological failure and resulted in unnecessary switches to second-line ART.…”
Section: Introductionmentioning
confidence: 99%
“…In the developing world, having to move from a first line regimen to a second line regimen increases the cost of ART tenfold (Sukasem et al, 2007;Sungkanuparph et al, 2007;Marconi et al, 2008). At present, third line regimens do not exist, meaning the development of resistance to second line regimens leaves patients without therapeutic options.…”
Section: Integrated Design and Process Technology Idpt 2009mentioning
confidence: 99%